Faktor-Faktor yang berhubungan dengan Pencapaian Kepuasan Layanan Masa Nifas - Dewi Susilawati; Nur Fadjri Nilakesuma (Universitas Batanghari Jambi, 2021)
One of the measuring tools for midwifery services is said to be of quality if a midwifery service can satisfy the client according to the level of satisfaction. Client satisfaction is influenced by internal factors and external factors. Internal factors come from the client himself (age, education, pregnancy distance, parity, and occupation) and external factors such as actions given by health workers. Client satisfaction is not only the responsibility of top management but has become the culture and commitment of all employees. The lower the quality of health services, the lower the level of patient satisfaction. The purpose of the study was to determine the factors associated with the achievement of postpartum service satisfaction. This type of research is an analytic description with a cross-sectional design. The sample of this study was postpartum mothers who received services from pregnancy to childbirth by midwives at Independent Practice Midwives (PMB) in Agam and Pasaman Regencies. The sampling technique was using accidental sampling with a period of 1 month, namely from July 1 to July 31, 2020, as many as 69 postpartum mothers. The data is processed by computer. Analysis of the data using the Chi-Square test. The results showed that the factors associated with postpartum service satisfaction were age, education level and service quality. Meanwhile, for parity and work factors, there is no relationship with postpartum service satisfaction. This study concludes that the variables associated with postpartum service satisfaction are age, education level and service quality, while parity and workers have no relationship with the respondent's level of satisfaction with the services they provide.